Effects of Chronic Manganese Exposure on Cognitive and Motor Functioning in Non-Human Primates - Schneider, Jay S. (2006)
Acute exposure to manganese is associated with complex behavioral/psychiatric signs that may include Parkinsonian motor features. However, little is known about the behavioral consequences of chronic manganese exposures. In this study, cynomolgus macaque monkeys were exposed to manganese sulfate (10 –15 mg/kg/week) over an exposure period lasting 272 ± 17 days. Prior to manganese exposure, animals were trained to perform tests of cognitive and motor functioning and overall behavior was assessed by ratings and by videotaped analyses. By the end of the manganese exposure period, animals developed subtle deficits in spatial working memory and had modest decreases in spontaneous activity and manual dexterity. In addition, stereotypic or compulsive-like behaviors such as compulsive grooming increased in frequency by the end of the manganese exposure period. Blood manganese levels measured at the end of the manganese exposure period ranged from 29.4 to 73.7 μg/L (mean = 55.7 ± 10.8 (compared to levels of 5.1–14.2 μg/L at baseline (mean = 9.2 ± 2.7), placing them within the upper range of levels reported for human environmental, medical or occupational exposures. These results suggest that chronic exposure to levels of manganese achieved in this study may have detrimental effects on behavior, cognition and motor functioning.